Juridical Analysis of Health Services for Elderly Hajj Pilgrims - Maikel, Mahesa Paranadipa; Syahruddin, Maslim (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2024)
Indonesia with the largest Muslim population causes the number of Muslims who registered to leave for the holy land to increase, including the number of elderly pilgrims in 1444 H/2023 M as many as 10,166 people from a total quota of 221,000 pilgrims. The Indonesian Ministry of Religious Affairs issued several special policies related to elderly pilgrims. The program is outlined in the